1999
DOI: 10.1046/j.1469-8137.1999.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungi associated with the temperate palm, Trachycarpus fortunei, within and outside its natural geographic range

Abstract: Fungal endophytes associated with the palm, Trachycarpus fortunei, within and outside its natural geographic range were investigated. Endophytes were relatively common with colonization rates of 23-57% at the four sites sampled. The endophyte assemblages at the different sites were diverse with 75 fertile species of ascomycetes and mitosporic fungi. The assemblage composition at each site was similar and between seven and 13 species comprised 81-89% of the taxa present in relative frequencies of 1%. Glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
89
1
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 39 publications
(97 reference statements)
7
89
1
4
Order By: Relevance
“…De Souza Sebastianes et al (2013) reported that the colonisation rate of endophytic fungi was significantly higher in branch than in leaf among three mangrove species in Brazil. The possible explanation might be that the structure and substrates are different between twig and leaf tissues, or that the twigs are more permanent than leaves, which influence the colonisation of endophytic fungi (Taylor et al 1999; Gilbert et al 2002; Wang and Guo 2007; Guo et al 2008). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De Souza Sebastianes et al (2013) reported that the colonisation rate of endophytic fungi was significantly higher in branch than in leaf among three mangrove species in Brazil. The possible explanation might be that the structure and substrates are different between twig and leaf tissues, or that the twigs are more permanent than leaves, which influence the colonisation of endophytic fungi (Taylor et al 1999; Gilbert et al 2002; Wang and Guo 2007; Guo et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…For example, Phomopsis fungi were widely isolated from mangroves (Suryanarayanan et al 1998; Suryanarayanan and Kumaresan 2000; Pang et al 2008; Xing et al 2011; Xing and Guo 2011) and non-mangrove plants (Taylor et al 1999; Guo et al 2000, 2008; Cannon and Simmons 2002; Murali et al 2006; Sun et al 2011, 2012). In addition, Pestalotiopsis as generalist fungi were common mangrove endophytes and widely occurred on plants across Palmae, Rhizophoraceae, Planchonellae, and Podocarpaceae in China (Liu et al 2010a, 2012; Xing and Guo 2011; Gong et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen percent of endophytes obtained from two Licuala species in Brunei and Australia, and 11% of isolates from the palm Trachycarpus fortunei in China were mycelia sterilia (Taylor et al, 1999 ;Fro$ hlich et al, 2000). Approximately 15% of endophytes isolated from evergreen shrubs in western Oregon (Petrini et al, 1982) and c. 26n9% of endophytes isolated from leaves of Sequoia sempervirens (coastal redwood) in central California were mycelia sterilia (Espinosa-Garcia & Langenheim, 1990).…”
Section: mentioning
confidence: 99%
“…This definition has been widely used throughout the literature and uses *Author for correspondence (tel j825 2975 5632 ; fax j852 2517 6082 ; e-mail kdhyde!hkucc.hku.hk). a traditional approach for the isolation of endophytes (Taylor et al, 1999). This approach involves surface sterilization of material and isolation of fungi from the internal parts.…”
Section: mentioning
confidence: 99%
“…They also represent a large reservoir of unexplored genetic diversity. They have been isolated from monocots, grasses [6], palms [7,16,23] rainforest plants [13] and few tropical plants [5,14,[19][20][21][22]. The practical applications of these endophytes are manifold; as potential biocontrol agents, sources of novel metabolites for therapeutics, plant protection, other industrial applications, and as model systems for studying the hostparasite interactions in natural ecosystems [18].…”
mentioning
confidence: 99%